Ressignificating theory of professional links in nursing work - Lisa Antunes Carvalho; Maira Buss Thofehrn; Edison Luiz Devos Barlem; Nara Jací da Silva Nunes
ABSTRACT Objective: to construct new meanings for the concepts of the Theory of Professional Links with the nursing staff in the micro workspace. Method: qualitative, descriptive and exploratory, based on Vygotsky's Historical-Cultural Theory. Eight care nurses from different care settings participated in the study. The data collection was conducted by the focus group technique and analysis by Minayo´ s operational proposal. Results: At the beginning of the resignification, some weaknesses have arisen for the application of the theory, among them: lack of time and physical space to meet with the teams, inexperience with approach and techniques of group dynamics. Spirituality and conflict management have emerged in the collective discourse contributing to the perfection of the theory. Conclusions and Implications for practice: from the theory application, there were gaps to be overcome both in the relational, technical and personal scope, allowing each nurse to visualize how their work process is given. Enables a reflective exercise on the doing and scope of group work and nurses' action and discourse in the management of interpersonal relationships. Through the new concepts added to the theory it can constitute a management model for nursing work.